ANALYSIS OF GREEN ECONOMY POLICIES IN PROMOTING ENVIRONMENTALLY FRIENDLY AGRICULTURAL PRACTICES AS A RESPONSE TO CLIMATE CHANGE - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
Increasingly evident climate change demands a strategic shift in agricultural practices to maintain environmental sustainability and food security. This article analyses green economy policies in promoting environmentally friendly agricultural practices as a response to climate change. The main focus lies on the application of environmentally friendly technologies, efficient resource management, and the integration of sustainable agricultural practices such as agroforestry and the use of organic inputs. The aim of this policy is to sustainably increase productivity while minimising negative impacts on the environment. In addition, this article highlights the importance of cross-sectoral collaboration between the government, research institutions, private organisations and farmers in achieving this goal. Through the support of this policy, it is expected to create an agricultural system that is more resilient to the challenges of climate change, while contributing to environmental conservation.